Sociocultural Learning Model for Empowering Sustainable Development Education in Islamic Boarding Schools through Local Cultural Contexts - Mgs. Muhammad Farouq; Rachmat Kriyantono; Muhammad Lukman Hakim; Sahiruddin (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2024)
Sustainable development has become an important concern for educational institutions around the world, with a growing emphasis on the integration of socio-cultural perspectives into the curriculum. This paper presents a critical analysis of the role of socio-cultural education in promoting education for sustainable development (ESD) within pesantren settings. It explores the key issues and challenges surrounding the incorporation of socio-cultural elements based on local wisdom. This research is entitled